Gossypiboma in a post caesarean patient: surgeon’s dilemma - Singh, Sonia Balbir; Sinha, Hemali H.; Jha, Sangam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Gossypiboma or retained surgical sponge is a relatively common, but underreported event due to medico legal implications and the exact incidence in not known. The clinical presentation and the time of presentation is variable because of which the diagnosis may be challenging. A high degree of suspicion is required to reach the diagnosis. Gossypiboma can have catastrophic implications for patients and healthcare professionals. We present a case of a 23-year old patient with retained surgical mop after caesarean section, who came with complaints of fever and pain abdomen. The purpose of presenting this case is to sensitize the surgeons to always keep retained surgical items as their differential diagnosis in cases of post-operative abdominal pain or fever, to decrease the time between surgery and diagnosis so as to minimize the morbidity to patient. The World health organization (WHO) surgical safety checklist should be strictly adhered to.